Retirement Need Analysis: How Much of My Current Income Will I Need for Retirement? FCS7251/FY1355, 3/2013 - Ruiz-Menjivar, Jorge; Gillen, Martie (EDIS, 2013)
The amount of money needed for retirement varies from person to person. There may not be an exact amount, but there are ways to estimate the amount you will need. While no “magic number” exists for the amount you should save for retirement, there are calculations you can use to estimate the amount you will need. Calculating your wage replacement ratio (WRR) using either the top-down or bottom-up approach can help you determine how much money you should put aside for retirement and provide you with savings goals. This 3-page fact sheet was written by Jorge Ruiz-Menjivar and Martie Gillen and published by the UF Department of Family Youth and Community Sciences, March 2013. http://edis.ifas.ufl.edu/fy1355